Determinan Kemiskinan Anak di Pulau Sulawesi, Maluku Dan Papua : Perspektif Pendidikan - Mohammad Hajir Suleman; Irawati Abdul; Fitri Hadi Yulia Akib (Economic Reviews Journal, 2025)
This study aims to analyze the factors influencing child poverty in Sulawesi, Maluku, and Papua, specifically focusing on the impact of education on poverty levels. Specifically, it identifies key determinants of child poverty, including formal education levels, literacy skills, and educational assistance programs (PIP), and examines how these variables influence a child's likelihood of experiencing poverty. The data utilized in this study were obtained from the National Socioeconomic Survey (Susenas KOR & KP 2023) conducted by Statistics Indonesia (BPS) and were analyzed using logistic regression methods. The findings indicate that children's education levels significantly reduce the likelihood of experiencing poverty. Children receiving educational assistance through the Program Indonesia Pintar (PIP) also have a lower probability of poverty, highlighting the effectiveness of this program in improving child welfare. However, literacy skills unexpectedly tend to increase the likelihood of child poverty, although this relationship is not statistically significant. Furthermore, preschool education does not significantly impact child poverty risk. These findings emphasize the need for child poverty alleviation policies in Sulawesi, Maluku, and Papua to focus on improving access to education and optimizing educational assistance programs to ensure a greater impact on child welfare. While the government has implemented various poverty alleviation policies, a more comprehensive and targeted implementation strategy is required, particularly for children from low-income families, by ensuring better access to education and effective support programs to reduce the risk of child poverty.